(untitled) (American Journal of Interdisciplinary Research and Innovation, 2022)
Green marketing is a process of producing environment friendly product. Such type of products that are safe from different hazards. The aim of the study is to measure the antecedents affecting consumers’ green purchase intention towards green products special reference with Nikaweratiya Divisional Secretary area, Kurunegala District. This study uses four dimensions as the independent variable of antecedents such as green purchase attitudes, green perceived values, green perceived trust, and ecological knowledge, while green purchase intention was taken as the dependent variable. For this study, 250 questionnaires were distributed. Further, the researcher used convenience sampling methods to select the sample from Nikaweratiya Divisional Secretariate area. The Pearson’s correlation analysis showed that the green purchase attitudes, green perceived values, green perceived trust and ecological knowledge had a medium positive relationship with green purchase intention. Regression analysis indicated that there was a significant positive impact on green purchase intention towards green products.